Dream catcher : a passion for people development - Tinashe, Mahupete (Emerald Publishing Limited : Information Age Publishing, 2019)
Succession planning at all levels of an organization is crucial.Dream Catcher is an established coaching program designed for anyone who wants to invest in helping others to reach their fullest potential. The program builds leaders with the capacity to fill key roles in organizations.The process is unique, simple, and concisely presented in this book.Dream Catcher is based on an approach that has been developed within and applied at QLI; a nationally renowned center of excellence in its field. QLI is based in Omaha, Nebraska, a city with a sub 3% unemployment rate. It is therefore essential for businesses to provide value for their developing team members in a manner that commands employee engagement leading to retention.Dream Catcher is based on neuroscience-backed theories. It is designed to assist coaches who will guide individuals and organizations to conquer challenges. Dream Catcher users become proficient in the art and science of creating compelling visions for their future selves, identifying what gaps exist in terms of skill sets, formulating plans to execute the vision, and establishing new habits to sustain the progress made.Those who follow this program not only learn how to be successful in attaining skills in specific areas or disciplines but can also apply the methods to other areas of their work and life. Dream Catcher is geared to be a way of life, not merely focused on short- term results.